Peer paired ranking: assessing and training 21st century graduates - Miralles, Cristóbal; Perelló-Marín, María Rosario; Canós-Darós, Lourdes; Vidal-Carreras, Pilar Isabel (Wydawnictwo Politechniki Łódzkiej, 2017)
In the context of European Higher Education, universities are highly adopting innovative curricula focused on students acquisition of skills and competences needed for the further career development of the 21st century graduates. Particularly, Universitat Politécnica de Valencia (UPV) (Spain), has launched an institutional Project on transversal skills UPV (i.e. skills acquired by the UPV graduates). This project is supported by the strategic plan UPV2020. Its main goal is to accredit, by using rubrics, 13 transversal skills of any graduate from the Universitat Politècnica de València. Within this paper, we work on one of the 13 transversal skills, particularly, critical thinking. Our aim is not just to assess the level of acquisition of this skill, but also to improve students’ performance. In so doing, an innovative computerbased tool is introduced based in ‘paired peer ranking’. It is also shown that peer assessment strengthens students skills, encourages participation, promotes academic excellence, and hence increases students’ performance, offers higher feed back, fosters attendance, and promotes greater accountability on the part of the students.[...]
Keywords: paired ranking; assessing; training; transversal skills; critical thinking; peer assessment; innovative "paired peer ranking" tool; improving student performance; umiejętności przekrojowe; krytyczne myślenie; ocena rówieśnicza; innowacyjne narzędzie "paired peer ranking"; poprawa wyników uczniów